First record of Craspedacusta sowerbii Lankester, 1880 (Cnidaria: Limnomedusae) in the Azores - Raposeiro, Pedro M. (2011)
[...]. This short communication, reporting the occurrence of C. sowerbii in the Congro Lake (São Miguel), is a result of the ongoing monitoring work of freshwater ecosystems performed by the University of Azores (e.g Gonçalves et al. 2008; Raposeiro & Costa 2009). Intense sampling has been carried out for the last six years in freshwater systems, but only now did we find this species.